Гадронна суперсиметрія з КХД - Catto, S.; Gürcan, Y.; Khalfan, A.; Kurt, L.; Nicolescu, B.; Yu, E. (Publishing house "Academperiodika", 2019)
The evolution of hadronic mass formulae with special emphasis on group theoretical descriptions and supersymmetry suggested by QCD and based on quark-antidiquark symmetry is shown, with further comments on possible applications to a Skyrme-type models that may compete with the potential quark models in the future.